SUN-LB041 Clinical and Molecular Characteristics, Genotype-Phenotype Correlation in 113 Chinese Children with SRD5A2 Gene Mutations - Fan, Lijun (J Endocr Soc, 2019)
Abstract Objective: Studies on 5α-reductase type 2 deficiency (5α-RD) are limited and the genotype-phenotype correlation has not been elucidated. The aim of the study was to analyze clinical and molecular characteristics, genotype-phenotype correlation in a large Chinese 5α-RD cohort. Design: Database registration study. Method: We analyzed clinical and genetic data of gene confirmed 5α-RD Children, comparing their phenotypes by using external masculinization score (EMS),the position of urethral meatus and gonads as well as penis length-standard deviation score (PL-SDS). Results: 85.84% of patients presented hypospadias while 14.16% had normal urethral meatus. When the cut-off value of stimulated T/DHT was 10 or 15, 98.48% and 92.42% of patients were diagnosed respectively. 8 patients with isolated micropenis were diagnosed as 5α-RD by higher T/DHT ratio and SRD5A2 gene mutations. There was no significant correlation between T/DHT and phenotypes (p>0.05). We identified 31 different variants including 10 unreported ones. The p.R227Q was the most prevalent variant (38.50%). The phenotypic indicators of patients with p.R227Q were higher than those without the mutation in multiple comparisons (p<0.05). Patients with the homozygous p.R227Q had milder phenotypes and larger standard deviation of phenotypic scores than those with other homozygotes. Conclusions: Subjects with 5α-RD can present isolated micropenis and T/DHT cannot foretell the severity of phenotypes. As a founder mutation in Chinese, the p.R227Q seems to link to relatively milder phenotypes and greater phenotypic variability. Variants can explain, at least partially, the heterogeneity of phenotypes, while other factors may also contribute to the phenotypes. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.